Experimental analysis of the addition of rice husk ash to the clayey subgrade of a road stabilized with lime - Vizcarra, S. (2020)
There are many studies about how the addition of lime and rice husk ash (RHA) gives the soil a better mechanical behavior, particularly on clayey soils, where usually fine particles reach more than 75%. However, the soils with a small presence of fine particles (59-60%) do not have much research. This analysis evaluates the influence that RHA has on this kind of soil stabilized with 3% of lime. After the initial mix of soil-lime, CBR increased 11.2 times its initial value; within the addition of the ash, the CBR averaged between 45-50% up until 28% of RHA was added, where the results decreased considerably. Soil workability improved and the specimens with more ash resulted in a more granular material, with a group index value 0 following the AASHTO standards. The greatest CBR record was obtained with the specimen of 16% RHA, 3% lime and soil, reaching a 51.3% CBR, 1.58g/cm3 of MDD and 16.5% of OMC. Yet, it only showed a 1.55% more resistance than the lime-soil specimen. The CBR with more presence of RHA tends to decrease its value, therefore for silica-rich clayey soils, the addition of lime by itself should be enough for an adequate performance.